Preparation method and application of hydrogel with three-dimensional structure
Through the methods of low-temperature printing and low-temperature cross-linking, the problems of narrow material application scope and poor versatility in the existing three-dimensional hydrogel manufacturing technology are solved, and the preparation of three-dimensional structure hydrogels with various material components is realized. It has good mechanical properties and high precision, and is suitable for integrated manufacturing of software devices and software robots.
Patent Information
- Application Number
- CN202411841590.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing three-dimensional hydrogel manufacturing technology has the problem of narrow application scope and poor versatility of materials, making it difficult to achieve integrated integration of complex devices and functions.
The method of low-temperature printing and low-temperature cross-linking is adopted to deposit and solidify the hydrogel precursor dispersion in the freezing space, and combined with the immersion process of the cross-linking bath, the hydrogel preparation of three-dimensional structure is achieved.
The preparation of three-dimensional structure hydrogels with various material components has been realized, with good mechanical properties and high precision, and is suitable for the integrated manufacturing of software devices and software robots.
Smart Images

Figure CN119552386A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrogel preparation, in particular to a preparation method and application of a hydrogel with a three-dimensional structure, and in particular to a preparation method of a hydrogel with multiple material components and a three-dimensional structure. Background Art
[0002] In recent years, hydrogel materials have shown great potential in the fields of biomedical engineering, wearable devices and underwater detection due to their unique advantages such as softness, low cost and biosafety due to their high water content. Soft devices and soft robots based on hydrogel materials are expected to bring rich functions and novel capabilities to scenarios such as bionic design, surgical intervention and artificial organs, and are currently a hot topic in academic research.
[0003] Due to the low density of the hydrogel's own polymer network and weak material interface bonding, traditional hydrogels are mostly integrated into devices in the form of planes and thin film patterns, which cannot realize complex devices and functions. The developed hydrogel 3D manufacturing technology is generally targeted at a single material or a single material system with the same molding mechanism, and the processing properties of the materials need to be adjusted one by one, which has the problems of narrow material application range and poor versatility.
[0004] Therefore, it is necessary to develop a universal preparation method for hydrogels with multiple material components and three-dimensional structures. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a hydrogel with a three-dimensional structure and its application in view of the problems existing in the prior art. The present invention is a simple and feasible method for preparing a hydrogel with a customizable three-dimensional structure and having a plurality of material components, so as to realize the integrated manufacturing of hydrogel soft devices and soft robots.
[0006] This traditional 3D printing method based on solute doping (specific photo- or thermal-polymerization reaction groups or rheological property modifiers) requires customized adjustment of the ink one by one, which is time-consuming and labor-intensive, and will result in the specificity of the cross-linking method, making it difficult for the heterogeneous structure to be integrated and cross-linked synchronously. At the same time, this solute doping will produce a component competition effect (that is, the mixture mainly exhibits the properties of its high-content component), which will weaken the properties of the polymer network body (stretchability, conductivity, etc.), while the present invention does not require the introduction of specific photo- or thermal-polymerization reaction groups or doping rheological property modifiers.
[0007] The purpose of the present invention can be achieved by the following scheme:
[0008] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0009] The present invention provides a method for preparing a hydrogel with a three-dimensional structure, comprising the following steps:
[0010] S1. Low temperature printing
[0011] The hydrogel precursor dispersion is deposited and solidified as required in a freezing space to form a crystalline structure;
[0012] S2, low temperature cross-linking
[0013] The crystalline structure is immersed in a cross-linking bath and cross-linked at low temperature to obtain a polymer structure, i.e., a three-dimensional hydrogel.
[0014] In the first step of the present invention, the solidification phase transition from liquid to solid of the hydrogel precursor dispersion in a low-temperature environment is used to realize the freezing and fixation of the shape. In combination with 3D printing, the deposited pattern can be programmed to realize the molding of the desired crystalline structure. In the second step, the antifreeze and other ingredients contained in the cross-linking bath diffuse into the crystalline structure immersed therein, causing the melting point of the crystalline structure to change. The slow melting of the ice crystals inside the crystalline structure in a low-temperature environment provides a liquid environment (solvent) for the cross-linking reaction. Low-temperature cross-linking can control the reaction kinetics rate, and is suitable for hydrogel precursors of different compositions to realize the transformation from crystalline structure to hydrogel structure.
[0015] As an embodiment of the present invention, in step S1, the hydrogel precursor dispersions of different compositions include dispersions of different hydrogel precursor materials and / or dispersions of different hydrogel precursor contents.
[0016] As an embodiment of the present invention, in step S1, the hydrogel precursor includes one or more of polyvinyl alcohol (PVA), sodium alginate (SA), poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS), chitosan, hyaluronic acid, and poly(N-isopropylacrylamide).
[0017] The present invention is mainly a cross-linking reaction, from the precursor (polymer chain) to the cross-linked network, and does not involve monomer polymerization. In the prior art, taking polyvinyl alcohol materials as an example, the precursor dispersion of such materials has strong fluidity, does not have thixotropic properties, and cannot undergo sol-gel transition. Conventional molding methods rely on mold-assisted molding, and cross-linking is achieved by freeze-thaw method or by adding low-concentration cross-linking agents to the precursor dispersion in advance, and it is impossible to directly 3D print the three-dimensional structure of polyvinyl alcohol hydrogel. Taking sodium alginate materials as an example, although such materials have sol-gel transition characteristics, their cross-linking mechanism mostly depends on calcium ion complexation, and has the limitations of fast cross-linking reaction rate and difficult regulation. The sodium alginate printed structure is directly immersed in the calcium ion cross-linking bath, and the external cross-linked area limits the penetration of calcium ions into the structure, resulting in uneven cross-linking of the structure and poor mechanical properties. Taking the heterogeneous structure composed of polyvinyl alcohol and sodium alginate as an example, the cross-linking mechanisms of the two materials are chemical cross-linking and physical cross-linking, respectively, and a single cross-linking bath component is difficult to achieve integrated synchronous cross-linking of heterogeneous structures.
[0018] As an embodiment of the present invention, in step S1, the solid mass fraction in the hydrogel precursor dispersion is 0.5%-15%, wherein polyvinyl alcohol is preferably 5-15%, sodium alginate is preferably 0.5-12%, and chitosan is preferably 2-6%.
[0019] The method of the present invention can be used for low mass fraction hydrogel precursor dispersions. When the viscosity is low, it cannot be used for conventional 3D printing. For example, 2% sodium alginate has a viscosity of only 1 Pa·s, which is lower than the viscosity required for conventional 3D printing and cannot be directly printed.
[0020] Different concentrations of hydrogel precursor dispersions have different rheological properties (mainly manifested as different viscosities, about 1-10000Pa s). The lower the solid content, the lower the viscosity, and the higher the fluidity of the dispersion. This type of dispersion requires rapid solidification after deposition to prevent line breakage and shape distortion caused by surface tension during processing. The higher the solid content, the denser the polymer network, and it is required to appropriately reduce the cross-linking reaction rate to ensure uniform cross-linking inside and outside. The method of freeze-drying cross-linking after freezing printing is usually difficult to achieve low solid content and complex overhanging structures, because such structures are prone to collapse due to ice crystal sublimation during the freeze-drying process, resulting in structural distortion. The present invention is immersed in a cross-linking bath, and the adjustable cross-linking reaction can regulate the material modulus to achieve structural self-support and avoid collapse caused by freeze-drying. The synchronous crystal melting and cross-linking reaction, as well as the buoyancy support of the cross-linking bath (the ice crystal sacrificial process provides buoyancy support) can ensure the fidelity of the structural shape. In addition, the freeze-drying method has low process adjustability, resulting in a single mechanical property of the material. The invention can adjust various process parameters such as cross-linking temperature, cross-linking agent content, cross-linking time, catalyst content, etc., so as to achieve wide-range adjustable mechanical properties (Young's modulus).
[0021] As an embodiment of the present invention, in step S1, the deposition and solidification method is 3D printing; 3D printing includes one or more of ink direct writing, inkjet printing, electrofluidic printing, and meniscus guided printing.
[0022] As an embodiment of the present invention, in step S1, the layout of the freezing space is one of a flat plate, a special-shaped curved platform, a cavity and a rotating shaft.
[0023] As an embodiment of the present invention, in step S1, the solvent in the hydrogel precursor dispersion includes one or more of water, ethanol, and dimethyl sulfoxide. The solvent is preferably a combination of water and other solvents. During the deposition and solidification process, the solvent can form crystals or achieve similar crystallization solidification by continuing to lower the temperature.
[0024] As an embodiment of the present invention, in step S1, the temperature of the deposition and solidification is lower than the crystallization temperature of the hydrogel precursor dispersion. The temperature is usually -5 to -30 degrees Celsius. If no subsequent cross-linking step is performed after low-temperature printing, the hydrogel structure will melt and collapse directly when placed at room temperature.
[0025] As an embodiment of the present invention, in step S1, when the deposition solidifies, the hydrogel precursor dispersions with different compositions are deposited in sequence, or the hydrogel precursor dispersions with different compositions are mixed and then deposited.
[0026] As an embodiment of the present invention, in step S2, the crosslinking bath is an aqueous solution including a crosslinking agent and an antifreeze agent. The crosslinking agent includes one of glutaraldehyde and a calcium-containing compound; when the crosslinking agent is glutaraldehyde, the antifreeze agent is ethanol and / or a calcium ion-containing compound; when the crosslinking agent is a calcium-containing compound, the antifreeze agent is ethanol.
[0027] The calcium ion-containing compound includes one or more of calcium chloride, calcium hydrogen phosphate and calcium carbonate. In the crosslinking bath, the molar concentration of glutaraldehyde is 0.0025-0.1 mol / L; the molar concentration of dilute hydrochloric acid is 0.01-0.5 mol / L; the mass fraction of calcium chloride is 0.5-10%; and the volume fraction of ethanol is 10-60%.
[0028] The hydrogel precursor includes polyvinyl alcohol, sodium alginate, chitosan, hyaluronic acid, and poly (N-isopropylacrylamide), and the crosslinking is carried out by a crosslinking agent or irradiation light initiation. The crosslinking is carried out by a crosslinking agent, and the crosslinking agent and antifreeze agent used are preferably the following combination:
[0029] The hydrogel precursor is polyvinyl alcohol, the cross-linking agent is glutaraldehyde, and the antifreeze agent is a calcium ion compound and / or ethanol.
[0030] The hydrogel precursor is sodium alginate, the cross-linking agent is a compound containing calcium ions, and the antifreeze agent is ethanol.
[0031] The hydrogel precursor is chitosan, the cross-linking agent is glutaraldehyde and / or a compound containing calcium ions, and the antifreeze agent is ethanol.
[0032] The hydrogel precursor is hyaluronic acid, the cross-linking agent is a compound containing calcium ions, and the antifreeze agent is ethanol.
[0033] The hydrogel precursor is poly(N-isopropylacrylamide), and the cross-linking is initiated by external irradiation light after immersion in an antifreeze bath; the antifreeze agent is a calcium ion compound or ethanol.
[0034] The crosslinking agent undergoes physical or chemical crosslinking reaction with the hydrogel precursor, and the antifreeze agent lowers the freezing point of the crosslinking bath to crosslink the frozen structure immersed therein under low temperature environment. During the low-temperature crosslinking process, the crosslinking agent and the antifreeze agent simultaneously diffuse into the pre-melted layer on the surface of the ice crystals inside the crystalline structure, achieving the simultaneous melting of the crystalline structure and the crosslinking reaction.
[0035] As an embodiment of the present invention, in step S2, the temperature of low-temperature crosslinking is higher than the crystallization temperature of the crosslinking bath used and lower than the melting temperature of the crystalline structure. The time of low-temperature crosslinking is 10 min-72 h.
[0036] As an embodiment of the present invention, in step S2, the polymer structure is further subjected to solvent post-treatment, wherein the polymer structure is immersed in a treatment bath (at room temperature) to obtain a hydrogel (having multiple material components and a three-dimensional structure).
[0037] Solvent post-treatment is a modification of the hydrogel structure obtained above, that is, the aggregation state of the hydrogel is regulated by the salt ions or acidic environment in the treatment bath to enhance its mechanical, electrical and other material properties. This step does not directly affect the formation of the hydrogel structure, but mainly enhances the performance of the hydrogel structure.
[0038] As an embodiment of the present invention, the post-treatment bath comprises one of deionized water, acid solution and salt solution. The immersion time of the polymer structure is 1-72 hours.
[0039] Acid solutions include dilute sulfuric acid, dilute hydrochloric acid, and acetic acid; salts include sodium citrate, sodium chloride, ferric chloride, sodium sulfate, ammonium sulfate, and diammonium phosphate.
[0040] The present invention also provides a device and application of the hydrogel prepared by the preparation method as a soft device and a soft robot.
[0041] The hydrogel obtained by the present invention is customized into a three-dimensional structure from a variety of material components as needed, the overall size of the structure is at the millimeter level, and the material is all hydrogel.
[0042] The present invention does not rely on photochemical reactions or thixotropic properties between solute materials, but uses low-temperature phase change of solvents to achieve structural molding, and is universal for different material components or hydrogel precursor dispersions of different concentrations. The present invention immerses the frozen structure in a low-temperature cross-linking bath to achieve cross-linking. Compared with the melting cross-linking based on temperature control, it delays the kinetic process of the cross-linking reaction, allowing multiple cross-linking agent components and multiple cross-linking mechanisms to react simultaneously, thereby achieving high-fidelity manufacturing of heterogeneous hydrogel structures. The present invention can achieve precise control of the hydrogel molding manufacturing process by changing the process parameters such as temperature and time of low-temperature printing and low-temperature cross-linking, and the structural properties of the manufactured hydrogel have a wide range of adjustability.
[0043] Compared with the traditional method (graded porous microstructure), the present invention utilizes the surface preferential crystallization mechanism of the hydrogel precursor dispersion under supercooling state. The surface of the prepared hydrogel structure has a submicron self-assembled polymer shell, and the inside of the shell has a uniform porous microstructure (mainly determined by the low-temperature printing temperature, and the cross-linking process is maintained as it is), and has a local anchoring structure and a material eutectic layer at the heterogeneous interface of the multi-material structure.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The present invention can realize a three-dimensional heterogeneous complex structure composed of multiple hydrogel material components with different cross-linking mechanisms without introducing specific photo- or thermal-polymerization reaction groups or doping rheological property regulators. The multi-material hydrogel obtained by the present invention has good mechanical properties and can withstand various deformation movements such as stretching, torsion, and extrusion without failure.
[0046] (2) The hydrogel structure obtained by the present invention has self-supporting geometric features including overhang, thin wall, hollow and high aspect ratio, as well as high precision and high shape fidelity, and can accurately realize the designed functions of soft devices including sensing and actuation. The present invention provides a general technical method for the integrated manufacturing of soft devices and soft robots. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0048] Figure 1 This is a photo of the three-dimensional crystal structure prepared in Example 3 of the present invention;
[0049] Figure 2 This is a photo of the three-dimensional hydrogel structure prepared in Example 3 of the present invention;
[0050] Figure 3 3 are stress-strain curves of the three-dimensional hydrogel structures prepared in Examples 1 and 3 of the present invention;
[0051] Figure 4 The stress-strain curves of the three-dimensional hydrogel structures prepared in Example 3 and Comparative Example 1 of the present invention;
[0052] Figure 5 This is a photo of the hydrogel structure prepared in Example 3 of the present invention attached to the joint of the back of the hand as a soft strain sensor (dilute hydrochloric acid 0.1 mol / L);
[0053] Figure 6 This is a microscopic image of the hydrogel structure obtained in Example 3, wherein a is the outer surface printed at low temperature, b is the cross-sectional edge printed at low temperature, c is the outer surface printed at room temperature, and d is the cross-sectional edge printed at room temperature.
[0054] Figure 7 A multi-material interface diagram of the three-dimensional structure of the hydrogel prepared in Example 3;
[0055] Figure 8 A sample cross-sectional view of the hydrogel structure prepared in Comparative Example 1;
[0056] Fig. 9 Schematic diagram of normal temperature printing in comparative example 2 (Figure a) and frozen printing in example 2 (Figure b);
[0057] Fig.10 This is a picture of the sample in Example 1 (12.5%wt polyvinyl alcohol portion, dilute hydrochloric acid 0.1 mol / L), wherein a is the hydrogel in Example 1, b is the hydrogel obtained by freeze printing and freeze drying, and c is the hydrogel obtained by freeze printing, freeze drying and cross-linking. DETAILED DESCRIPTION
[0058] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0059] Example 1
[0060] (1) preparing polyvinyl alcohol (PVA) and sodium alginate (SA) solids into 12.5% wt and 4% wt aqueous dispersions respectively;
[0061] (2) extruding the aqueous dispersion obtained in step (1) onto a freezing plate at -20 degrees Celsius as required by means of an ink direct writing device, and solidifying it to form a multi-material crystalline structure;
[0062] (3) glutaraldehyde at a molar concentration of 0.1 mol / L, dilute hydrochloric acid at molar concentrations of (0.032, 0.1, 0.32 mol / L), and calcium chloride at a mass fraction of 10% wt were added to a 30% volume fraction ethanol aqueous solution to prepare a crosslinking bath;
[0063] (4) immersing the crystalline structure obtained in step (2) in the cross-linking bath obtained in step (3) at -10 degrees Celsius for 12 hours to prepare a polymer structure;
[0064] (5) placing the hydrogel structure obtained in step (4) in deionized water for 24 hours to obtain a hydrogel structure.
[0065] The stress-strain curve of the multi-material three-dimensional hydrogel structure (12.5%wt polyvinyl alcohol part, dilute hydrochloric acid 0.1 mol / L) is shown in Figure 3 shown.
[0066] like Fig.10 As shown (all are partial hydrogels prepared from dilute hydrochloric acid 0.1 mol / L and 12.5%wt polyvinyl alcohol), the hydrogel of Example 1 is shown as 10a, and the hydrogel obtained according to the freeze printing and freeze drying steps of Comparative Example 1 is shown as 10b, and further cross-linked as shown in 10c.
[0067] Example 2
[0068] (1) preparing polyvinyl alcohol solid into 1%wt, 2%wt and 5%wt aqueous dispersions respectively;
[0069] (2) spraying the aqueous dispersion obtained in step (1) onto a freezing shaft at -10 degrees Celsius as required by means of an inkjet printing device, and solidifying the solution in turn to form a crystalline structure;
[0070] (3) adding glutaraldehyde and dilute hydrochloric acid at a molar concentration of 0.5 mol / L into a 20% by volume ethanol aqueous solution to prepare a crosslinking bath;
[0071] (4) immersing the crystalline structure obtained in step (2) in the cross-linking bath obtained in step (3) at -5 degrees Celsius for 24 hours to prepare a polymer structure;
[0072] (5) placing the hydrogel structure obtained in step (4) in a 1.5 mol / L saturated sodium citrate solution for 2 hours, and washing with deionized water to obtain a hydrogel structure.
[0073] Example 3
[0074] (1) Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) particles and polyvinyl alcohol (PVA) particles were respectively prepared into 7% wt aqueous dispersion and mixed in a ratio of 2:3;
[0075] (2) preparing polyvinyl alcohol particles into a 10%wt aqueous dispersion;
[0076] (3) The aqueous dispersions obtained in steps (1) and (2) are sequentially deposited on a shaped frozen curved surface at minus 30 degrees Celsius by means of an ink direct writing device, and solidified to form a crystalline structure, such as Figure 1 As shown;
[0077] (4) adding glutaraldehyde and dilute hydrochloric acid at a molar concentration of 0.1 mol / L and calcium chloride at a mass fraction of 20% wt into deionized water to prepare a crosslinking bath;
[0078] (5) immersing the crystalline structure obtained in step (3) in a cross-linking bath obtained in step (3) at -10 degrees Celsius for 8 hours to prepare a polymer structure;
[0079] (6) The hydrogel structure obtained in step (5) is placed in 5 mol / L dilute sulfuric acid for 1 hour, and then washed with deionized water to obtain a hydrogel structure.
[0080] The obtained multi-material three-dimensional hydrogel structure photos are as follows Figure 2 The stress-strain curve of the multi-material three-dimensional hydrogel structure is shown in Figure 3 shown.
[0081] like Figure 4 As shown, the mechanical properties (elongation, mechanical modulus) of the hydrogel (10%wt polyvinyl alcohol part) prepared by the method of the present invention vary with different hydrochloric acid contents, showing a wide range of adjustable properties. The hydrogel dispersion was freeze-printed and freeze-dried according to the steps of Comparative Example 1, and further cross-linked for comparison. The elongation at break of the hydrogel prepared by the method of the present invention (Example 3) was increased by about four times compared with the comparative example, and it also had low modulus characteristics (Young's modulus was reduced by one order of magnitude), which can better provide a self-supporting structure for soft robot applications.
[0082] The obtained hydrogel structure (dilute hydrochloric acid 0.1 mol / L) is attached to the joint of the back of the hand as a soft strain sensor. Figure 5 shown.
[0083] The hydrogel structure obtained by the method of the present invention is as follows Figure 6 a(outer surface), Figure 6 As shown in b (cross-section edge), the surface phase change leads to the formation of a polymer shell. However, after the aqueous dispersion of this example is printed at room temperature, it is cross-linked at low temperature to present a hierarchical porous structure (6c, d).
[0084] The hydrogel structure obtained by the method of the present invention is as follows Figure 7As shown, the multi-material interface is clear and there is an anchoring structure between the layers. The clear heterogeneous material interface can ensure that the structure accurately performs the specific tasks of the software device according to the designed material and functional partitions. At the same time, the stress and strain are reasonably distributed at the interface, avoiding local stress concentration caused by unclear interfaces between materials and reducing the fragility or failure risk of the structure.
[0085] Comparative Example 1: Freeze printing-low temperature freeze drying-low temperature cross-linking
[0086] (1) poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS) particles and polyvinyl alcohol particles were respectively prepared into 7% wt aqueous dispersions and mixed uniformly at a ratio of 1:3;
[0087] (2) preparing polyvinyl alcohol particles into a 10%wt aqueous dispersion,
[0088] (3) depositing the aqueous dispersions obtained in steps (1) and (2) on a frozen plate at -15 degrees Celsius in sequence as required by means of an ink direct writing device, and solidifying them to form a crystalline structure;
[0089] (4) freeze-drying the crystalline structure obtained in step (3) at -80 degrees Celsius and 10 Pascal pressure for 48 hours to prepare a freeze-dried sample;
[0090] (5) The partially crystalline structure obtained in step (2) was immersed in the cross-linking bath obtained in Example 3 for 8 hours to prepare a polymer structure.
[0091] like Figure 8 As shown, the cross-section of the sample that was directly freeze-dried after low-temperature printing has a dense interior, collapsed pores, and an uneven surface.
[0092] Comparative Example 2: Normal Temperature Printing
[0093] The preparation method of this comparative example is substantially the same as that of Example 2, except that a 5 wt % aqueous dispersion of polyvinyl alcohol is used and printing is performed at room temperature.
[0094] like Fig. 9 As shown in (Figure a, Figure b is Example 2), the hydrogel structure cannot be formed.
[0095] Comparative Example 3: Cryoprinting-Room Temperature Crosslinking
[0096] The preparation method of this comparative example is basically the same as that of Example 1, except that the cross-linking step is carried out at room temperature (25° C.).
[0097] The crystalline structure of this comparative example melts at room temperature, and collapses and distorts under the action of gravity and surface tension. The resulting cross-linked product has a large Young's modulus and exhibits strong mechanical brittleness, and the uneven degree of cross-linking reaction causes the product to warp due to internal stress.
[0098] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a three-dimensional hydrogel, characterized in that: The steps include: S1. Low temperature printing The hydrogel precursor dispersion is deposited and solidified as required in a freezing space to form a crystalline structure; S2, low temperature cross-linking The crystalline structure is immersed in a cross-linking bath and cross-linked at low temperature to obtain a polymer structure, i.e., a three-dimensional hydrogel.
2. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S1, the hydrogel precursor includes one or more of polyvinyl alcohol, sodium alginate, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), chitosan, hyaluronic acid, and poly(N-isopropylacrylamide).
3. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S1, the hydrogel precursor dispersions are dispersions of hydrogel precursors of different compositions; the dispersions of hydrogel precursors of different compositions include dispersions of different hydrogel precursor materials and / or dispersions of different hydrogel precursor contents.
4. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S1, the deposition and solidification method is 3D printing; 3D printing includes one or more of ink direct writing, inkjet printing, electrofluidic printing, and meniscus guided printing.
5. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S1, the solvent in the hydrogel precursor dispersion includes one or more of water, ethanol, and dimethyl sulfoxide.
6. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S1, the deposition and solidification temperature is lower than the crystallization temperature of the hydrogel precursor dispersion.
7. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S2, the cross-linking bath is an aqueous solution including a cross-linking agent and an antifreeze agent.
8. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S2, the temperature of low-temperature cross-linking is higher than the crystallization temperature of the cross-linking bath used and lower than the melting temperature of the crystalline structure.
9. The method for preparing a three-dimensional hydrogel according to claim 1, characterized in that: In step S2, the polymer structure is also post-treated with a solvent; The solvent post-treatment step is: immersing the polymer structure in a treatment bath to obtain a hydrogel; the post-treatment bath comprises one of deionized water, an acid solution, and a salt solution.
10. Use of the hydrogel obtained by the preparation method as claimed in claim 1 in soft devices and soft robots.
Citation Information
Patent Citations
Cryogel 3D scaffolds and methods for producing thereof
CN110177584A
Mixed hydrogel capable of being co-extruded and co-molded and method for 3D printing of hydrogel stent
CN114470336A